Micro-structured tungsten, a high heat flux pulse proof material. (December 2020) - Terra, A.; Sergienko, G.; Kreter, A.; Martynova, Y.; Rasiński, M.; Wirtz, M.; Loewenhoff, Th.; Pintsuk, G.; Dorow-Gerspach, D.; Mao, Y.; Schwalenberg, D.; Raumann, L.; et al.
Highlights: Improving tungsten thermal cycling handling capabilities and reducing cracks occurring as plasma facing material (PFM). Development of new structured tungsten at micron scale. Testing and evaluation of its performances as a PFM and under degraded state. Abstract: Micro structured tungsten is a new approach to address one of the main issues of tungsten as high heat flux (HHF) plasma facing material (PFM), which is its brittleness and its propensity to crack formation under pulsed, ELM like, heat loads (Loewenhoff et al., 2015; Wirtzet al., 2015 [2, 3]). With power densities between 100 MW/m 2 and 1 GW/m 2, progressive thermal fatigue induced damages like roughening, subsequent cracking and even melting will occur in dependence on the pulse number and PFM base temperature. This represents a serious issue for the usage of tungsten as HHF-PFM. In future tokamaks, such as ITER, about 10 8 ELMs are expected to occur during the operational lifetime. Several approaches have been tried to overcome this brittleness issue, e.g. alloying tungsten with others elements (Linsmeier et al., 2017 [4]) or introducing pseudo-ductility due to the additions of fibres thus creating composites (Reiser et al., 2017 [5]). Micro-structured tungsten showed a significant improvement in comparison with any of these approaches with respect to the damage expected by ELMs. This investigation on both bulk reference and micro-structured tungsten was performed in the PSI-2 facility (Kreter et al., 2015 [8]). A sequential load was applied combining steady state deuterium plasma (5.1 × 10 25 D + m −2, 51 eV, 240 °C, 150 min) loading with laser pulses (up to 10 5 pulses of 0.5 GW/m 2, 3.6 mm spot diameter, 20 J, 1 ms pulse duration, up to 25 Hz pulse frequency). In contrast to reference bulk tungsten, none of the applied loading conditions caused any evident damage on the micro-structured tungsten. The maximum surface temperature within the loaded area measured with a fast pyrometer was increased by about 800 °C at the end of the laser exposure for the reference sample. This is related to the emissivity changes and local temperature increase caused by surface degradation. Meanwhile, the micro-structured sample did not show any change of its temperature response from the 10th to the 100 000th pulse.